Nivolumab-induced myasthenia gravis in a patient with squamous cell lung carcinoma: Case report. Issue 27 (July 2017) - Chen, Yu-Hsiu; Liu, Feng-Cheng; Hsu, Chang-Hung; Chian, Chih-Feng
Abstract: Rationale: Nivolumab (Nivo) is an immune checkpoint inhibitor that has been used to treat advanced melanoma, nonsmall cell lung carcinoma, and renal cell carcinoma since 2015. Nivo is associated with several side effects, including hepatitis, pneumonitis, acute renal failure, endocrine disorder, and other immune-related adverse events. Here, we describe the case of a 65-year-old man with squamous cell lung carcinoma who developed myasthenia gravis (MG) after a third Nivo infusion. Patient concerns: A 65-year-old man with advanced squamous cell lung carcinoma developed ptosis, diplopia, drop head, and general weakness 5 days after a third Nivo infusion. Diagnoses, interventions, and outcomes: We diagnosed him with Nivo-related MG and myositis based on clinical symptoms, elevation of muscle enzymes, negativity for autoantibodies and exclusion of other diagnoses. Steroid treatment with methylprednisolone 1 mg/kg/d and pyridostigmine 60 mg twice a day was administered beginning at admission; however, the patient's condition progressively worsened, despite treatment. Respiratory failure developed 2 weeks after admission, and his family declined the use of a mechanical ventilator. The patient died on day 27 after the third Nivo infusion. Lessons: Nivo-related MG should be highly suspected in patients who develop ptosis, diplopia, and general weakness. The corresponding treatments include discontinuation of Nivo and steroid treatment with plasmapheresis. The disease course may be rapid and fatal. This report stresses the importance of awareness of this rare and lethal adverse effect while using nivolomab immunotherapy.